Gender Discrimination in Property Rights - Marco Casari; Maurizio Lisciandra (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
In the Middle Ages women in the Italian Alps had substantially more rights on collective properties than in the Modern Age. The documental evidence shows a progressive erosion of women's rights and a convergence toward gender-biased inheritance systems. We tracked the evolution of inheritance regulations on collective land in the peasant communities of Trentino over a period of six centuries (13th-19th). Considering a panel of hundreds of communities, we provide a long-term perspective of institutional change. When population pressure increased, a patrilineal system emerged as a protective measure to preserve the per-capita endowment of collective properties within a community. This study raises general issues about the role of local level versus centralized decision-making in delivering gender equality and about the long-term trade-off between the protection of common resources and a healthy genetic pool at the community level.
Keywords: J16; N53; Q20; 330